(3eSfO GdGeGe GdTGaYi QVi Gddg Yfgs - (3CHh YHO Gddg eMeO Hf GOQjS GdTGaYjs ((3YehOi Hf bGSe GHf eMeO GdYQGbi s)
(3ChdgG (B:s
(3jbhd GdYHO GdabjQ YHO Gddg Hf eMeO Hf CMeO aVd GdMVQei GdSYOi bGd Cf GdTGaYi bGd Ef edc Yf UahGf abGd jG QShd Gddg EfG fQcH GdHMQ hfMed eYfG Gdbdjd GdeGA aEf JhVGfG Hg YWTfG s
(3BNQgG (B:s
(3bGd GdTGaYi Yf CHj YHO Gddg Efg CJi Ydi GdUaG ai YeQI HYO eG WGa HGdHjJ BNQ SeO GdEeGe s
(3HChdgG aGFOIs
(3HgG fXGe GdJYbjHIs
(3QhGjI YHO Gddg Hf eMeO Hf CMeO aVd GdMVQei GdSYOi cX (B2 / 1680s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs